2003
DOI: 10.1359/jbmr.2003.18.5.876
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 8-Month Vertical Whole Body Vibration on Bone, Muscle Performance, and Body Balance: A Randomized Controlled Study

Abstract: Recent animal studies have given evidence that vibration loading may be an efficient and safe way to improve mass and mechanical competence of bone, thus providing great potential for preventing and treating osteoporosis. Randomized controlled trials on the safety and efficacy of the vibration on human skeleton are, however, lacking. This randomized controlled intervention trial was designed to assess the effects of an 8-month whole body vibration intervention on bone, muscular performance, and body balance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
201
1
22

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(237 citation statements)
references
References 50 publications
13
201
1
22
Order By: Relevance
“…Efforts to exploit bone's mechanosensitivty to strengthen the skeleton and to retard diseases such as osteoporosis have involved exercise 1,2 and external loading 3,4 regimes, albeit with varying levels of clinical success. 5,6 Differences in the anabolic and anti-catabolic capacity of different exercise regimes, such as between swimming and high-impact exercise, have often been attributed to differences in the induced matrix deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to exploit bone's mechanosensitivty to strengthen the skeleton and to retard diseases such as osteoporosis have involved exercise 1,2 and external loading 3,4 regimes, albeit with varying levels of clinical success. 5,6 Differences in the anabolic and anti-catabolic capacity of different exercise regimes, such as between swimming and high-impact exercise, have often been attributed to differences in the induced matrix deformation.…”
Section: Introductionmentioning
confidence: 99%
“…As we become more knowledgeable concerning what bone is most responsive to, in terms of stimulating mechanical adaptation, it does not appear that a larger signal is necessarily better, especially when considering that larger signals are associated with an increased risk of tissue damage. Other studies that have administered LIV have been shown to be safe, [12][13][14][15] and these prior reports have demonstrated potential to increase trabecular bone density and improve bone strength in animal studies, [16][17][18]32,33 with benefits to both bone and muscle. 14,18 In a rat model of disuse with constant hind limb suspension compared with normal weight-bearing animals, LIV administered at 90 Hz and 0.25 g on the hind limb suspended rats for 10 minutes a day, 5 days per week, successfully maintained normal rates of bone formation; experimental animals had suppressed bone formation rates of 72% compared to weight-bearing control animals.…”
Section: Discussionmentioning
confidence: 92%
“…Pharmacological approaches to prevent bone loss have not been generally accepted as efficacious, and they are not routinely administered. 10,11 However, low-magnitude mechanical signals of lowintensity vibration (LIV) delivered by an oscillating platform have been shown to be safe, [12][13][14][15] easy to administer, and anabolic to bone in both animal [16][17][18][19] and human studies. 14,20 This preliminary evidence, although not yet studied in persons with SCI, has demonstrated efficacy in reducing or preventing bone loss in persons with low bone density, as reported in postmenopausal women 14 and children with cerebral palsy.…”
Section: Introductionmentioning
confidence: 99%
“…Investigators [5][6][7][8] have studied SAV in humans to determine its effects on strength and balance. Torvinen et al 9 reported that a single bout of SAV comprising 4 minutes at a frequency of 15 to 30 Hz, amplitude of 0.72 to 10 mm, and acceleration of 3.5 to 14g rapidly improved muscle performance of the lower extremities and body balance in young healthy adults.…”
Section: Researchersmentioning
confidence: 99%